THE IMPORTANCE OF INCLUSIVE EDUCATION IN THE PROCESS OF CONTINUOUS PROFESSIONAL DEVELOPMENT (Web of Teachers: Inderscience Research, 2023)
This article provides information about continuing education, its principles, professional development of continuing professional development through the continuing professional education platform, and the importance of inclusive education in the process of continuing professional development.